Exploration of latent early literacy profiles in German kindergarten children using a newly developed app - Stuhr, Christina; Yumus, Melike; Meindl, Marlene; Jungmann, Tanja; Hughes, Charmayne Mary Lee (Frontiers in Education, 2024)
Introduction This study explores the effectiveness of the tablet-based EuLeApp© assessment tool in identifying distinct latent early literacy profiles among German kindergarten children aged between 4.0 and 7.0 years. Additionally, the study investigates how factors such as age, biological sex, and language impairment contribute to the manifestation and prevalence of these latent literacy profiles. Methods Utilizing latent class analysis on a diverse sample of 285 children, we administered a prototype of the EuLeApp© assessment tool to measure early literacy skills (i.e., print awareness, concepts of print, word awareness, phonological awareness, alphabet knowledge, and narrative skills). The sample included children aged between 4.0 and 7.0 years from various demographic backgrounds. Analysis involved identifying distinct early literacy profiles based on the assessment results. We also examined the influence of age, biological sex, and language impairment on the manifestation and prevalence of these profiles. Results The analysis revealed four stable and interpretable early literacy profiles: Exceptional Performers (17%), Typical Performers (41%), Marginal Performers (35%), and Subpar Performers (7%). These profiles were found to be shaped by the complex interplay of age, biological sex, and language impairment status among the children. Discussion These findings underscore the importance of employing person-centered methodologies to characterize early childhood literacy profiles, providing a framework for tailoring intervention programs to suit the unique characteristics and requirements of individual children.